Nitrous oxide production and isotopomer composition by fungi isolated from salt marsh sediments - Lazo-Murphy, Birch Maxwell; Larson, Samantha; Staines, Sydney; Bruck, Heather; McHenry, Julianne; Bourbonnais, Annie; Peng, Xuefeng (Frontiers in Marine Science, 2022)
The emissions of nitrous oxide (N2O), a potent greenhouse gas and ozone-depleting agent, have been steadily increasing from coastal environments, such as salt marsh sediments, as a result of anthropogenic nutrient loading. Biotic processes, including nitrification and denitrification, are the largest sources of N2O from salt marsh sediments. While it is assumed that the bulk of N2O from salt marsh sediment is produced by nitrification and bacterial denitrification, recent reports suggest fungal denitrification may contribute significantly. In this study, four fungi capable of growth under sulfidic conditions were isolated from salt marsh sediments in North Inlet, South Carolina, USA. Fungal species included Purpureocillium lilacinum, Trichoderma harzianum, Trichoderma virens, and Rhodotorula glutinis, as determined by sequencing the18S and 28S rRNA genes. The isotopomer signatures of N2O produced by these fungi were measured using isotope ratio mass spectrometry, which can be used to estimate the contribution of different sources of N2O. Up to 22.8% of nitrite provided in growth media was converted to N2O by fungal strains isolated from salt marsh sediments. The site preference (SP) of N2O produced by salt marsh sediment fungi ranged from 7.5 ± 1.6‰ to 33.4 ± 1.2‰. These values are lower than the SP of N2O from the model fungal denitrifier Fusarium oxysporum (37.1 ± 2.5‰), which is the SP typically used as an endmember in isotope mass balance considerations. The N2O SP values we measured expand the range of N2O SP used for isotope mass balances calculations to determine the relative contribution of fungi to N2O production in salt marsh sediments.